1999
DOI: 10.1046/j.1365-2443.1999.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Similar and differential behaviour between the nectin‐afadin‐ponsin and cadherin‐catenin systems during the formation and disruption of the polarized junctional alignment in epithelial cells

Abstract: Background: We have recently identi®ed a novel cellcell adhesion system, named NAP system, which is localized at cadherin-based cell-cell adherens junctions (AJs). The NAP system is composed of at least nectin, afadin and ponsin. Nectin is an immunoglobulin-like cell adhesion molecule. Afadin is an actin ®lament-binding protein which associates nectin with the actin cytoskeleton. Ponsin is an afadin-binding protein which furthermore binds to vinculin and provides a possible linkage of nectin-afadin to cadherin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 38 publications
6
88
0
1
Order By: Relevance
“…At the next stage, small cell ± cell junctions are formed at the tips of these cellular protrusions, which are regarded as spot-like primordial junctions as previously reported (Yonemura et al, 1995). Nectin-2 is concentrated at these small contact sites (Asakura et al, 1999). We con®rmed here these earlier observations.…”
Section: Inability Of Mlin-7c To Interact Directly With Nectin or Afadinsupporting
confidence: 89%
See 2 more Smart Citations
“…At the next stage, small cell ± cell junctions are formed at the tips of these cellular protrusions, which are regarded as spot-like primordial junctions as previously reported (Yonemura et al, 1995). Nectin-2 is concentrated at these small contact sites (Asakura et al, 1999). We con®rmed here these earlier observations.…”
Section: Inability Of Mlin-7c To Interact Directly With Nectin or Afadinsupporting
confidence: 89%
“…Wound healing assay of MTD-1A cells was performed as described (Ando-Akatsuka et al, 1999;Asakura et al, 1999). Brie¯y, MTD-1A cells (5.0610 5 cells) were seeded on a 18-mm glass coverslip (Matsunami, Osaka, Japan) and cultured for about 48 h to be con¯uent.…”
Section: Other Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting finding was that CLMP was recruited to plasma membrane protrusions and early cellular contacts between subconfluent cells. Earlier studies have shown that ZO-1 co-localizes together with cadherin, nectin and AF-6 in such primordial junctions (36,37). As polarization proceeds, claudin and occludin gradually accumulate at the ZO-1 positive, spot-like junctions, to form belt-like TJs.…”
Section: Discussionmentioning
confidence: 91%
“…We have obtained several lines of evidence that the nectin-afadin system plays an important role in the formation of AJs in cooperation with the E-cadherincatenin system: (1) the nectin-afadin system is strictly con®ned to AJs, which are undercoated with F-actin bundles in polarized epithelial cells, whereas the Ecadherin-catenin system is more widely distributed from AJs to the basal area along the lateral membrane (Mandai et al, 1997;Takahashi et al, 1999); (2) studies using afadin (7/7) mice and (7/7) embryoid bodies indicate that the proper organization of AJs and TJs are markedly impaired in epithelial cells (Ikeda et al, 1999); (3) cadherin-de®cient L ®broblasts stably expressing nectin-1 (nectin-1-L cells) form cell ± cell adhesion in an E-cadherin-independent manner, and the nectin-1-afadin system recruits the E-cadherincatenin system without the formation of the transdimmer of E-cadherin to the nectin-1-based cell ± cell adhesion formed between nectin-1-L cells and L cells stably expressing both E-cadherin and nectin-1 (nectin-1-EL cells) ; and (4) at the initial stage during the formation of AJs and TJs, primordial spot-like cell ± cell junctions are ®rst formed at the tips of the cellular protrusions radiating from adjacent cells (Yonemura et al, 1995;Ando-Akatsuka et al, 1999;Adams et al, 1998;Vasioukhin et al, 2000), and the E-cadherin-catenin and nectin-afadin systems colocalize to the primordial junctions where claudin is not concentrated (Ando-Akatsuka et al, 1999;Asakura et al, 1999;. Consistent with our results, nectin-1 has recently been determined by positional cloning to be responsible for cleft lip/palate-ectodermal dysplasia, which is characterized by cleft lip/palate, syndactyly, mental retardation, and ectodermal dysplasia (Suzuki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%